AWARENESS ABOUT FLUORIDATED TOOTHPASTES AMONG DENTAL STUDENTS - A QUESTIONNAIRE SURVEY - Preethi Raj M, Dhanraj Ganapathy, L. Keerthi Sasanka (Drugs and Cell Therapies in Hematology, 2022)
BACKGROUND: Modern dentistry moves towards preventive dentistry which has decreased prevalence of caries. The aim of this study is to analyse the awareness about fluoridated toothpastes among dental students. The objective of this study is to determine and analyse the brushing methods, ingredients present in it, benefit on fluoridation, protection, prevention and alternation about fluoridation. MATERIALS AND METHODS: A cross sectional survey containing 10 questions was conducted through google forms. These questionnaires were framed based on knowledge and awareness about fluoridated toothpastes among dental students and the responses were received from 177 participants. SPSS Software version 21 was used, chi square test was analysed and the responses were tabulated. RESULT: In this survey, about 68.36% of people said they brush twice a day. Majority of people ( 77.40% ) say that adults benefit from fluoridation and 69.32% suggest that fluoride prevents cavities and makes teeth strong. However statistically non significant difference between the genders with respect to awareness on fluoridation tooth pastes and practices (P>0.05) CONCLUSION: The study population has a routine habit of using fluoridated toothpastes and their opinion of using fluoridated toothpaste regularly was effective in maintaining their oral health.